Perfil e digestibilidade de farinhas de insetos avaliadas com galos cecectomizados - Oliveira, Maiara Rodrigues Duarte de (2018)
Insects are a potential source for replacing protein foods and have a market potential similar to the fishmeal market, but more sustainable and with promising nutritional qualities for the future need in animal nutrition and because they have different eating habits, they can be created with by-products and residues. The objective of this study was to evaluate the composition and digestibility of amino acids, dry matter digestibility, true digestible amino acids and the profile of ideal protein of three insect meal for use in dog and cat feeding. The experiment was conducted at the Department of Animal Science at the University of Illinois, located in Urbana-Champaign, United States. Sixteen Leghorn white roosters were used and all birds were fed using the forced feeding method described by Sibbald (1979). The roosters were distributed in a completely randomized design. At the beginning of the experiment, the cecectomized roosters were fasted for 24 hours before being intubated to receive the treatment. Each rooster received 30g of the corresponding treatment and after intubation the animals were fasted again. Excreta collection was done using plastic trays under the cages of each bird, for 48 hours. The excreta were lyophilized, weighed and ground in a 0.25mm sieve. Amino acid concentrations were measured in each sample. Endogenous amino acid excretion was measured using 4 roosters fasted for 48 hours. The standardized digestibility of the amino acid was calculated by the method described by Sibbald (1979). The bromatological analyzes of the three meals were carried out at the DZO / UFLA Animal Research Laboratory. Regarding the study statistics, the data were analyzed by ANOVA (SAS Inst. Inc.) as a completely randomized design. Differences in treatment were determined using the LSD procedure calculated from the ANOVA SEM. A probability of P <0.05 was used to declare statistical significance. The Madagascar hissing cockroach meal had the highest total amount of amino acids. The largest quantities of essential amino acids were those presented by the morioworms meal and was the only one that showed levels of taurine. For the non-essential amino acids, the Madagascar hissing cockroach meal presented the highest values when compared to the morio worms. Methionine was the only amino acid where no differences (P >0.05) in digestibility were observed between the meals. The highest values of the digestibility were found for the birds fed the morio worms meal. Regarding the digestibility of dry matter (DM), the morio worms and the lobster cockroach meals did not present differences between them (P >0.05), being these larger than the one presented by Madagascar hissing cockroach. The morioworms meal also had the highest digestible amino acid values except for methionine and arginine. For dog feeding, Madagascar hissing cockroach meal presented limitation for tryptophan, the morioworms meal for threonine and the lobster cockroach meal for tryptophan and threonine. As for cats, all the meals presented limitations for leucine, threonine and arginine and tryptophan for Madagascar hissing cockroach and lobster cocoroach meals. It is concluded that among the treatments the three insect meals obtained good results, but the morio worm meal was the one that showed the best. Nevertheless, the results of this study show that the three insect meals are adequate substitutes for the commonly used protein sources.